Attribute-based encryption scheme supporting attribute revocation in cloud storage environment - Lei SUN; Zhiyuan ZHAO; Jianhua WANG; Zhiqiang ZHU (Tongxin xuebao)
Attribute-based encryption (ABE) scheme is widely used in the cloud storage due to its fine-grained access control.Each attribute in ABE may be shared by multiple users at the same time.Therefore,how to achieve attribute-level user revocation is currently facing an important challenge.Through research,it has been found that some attribute-level user revocation schemes currently can’t resist the collusion attack between the revoked user and the existing user.To solve this problem,an attribute-based encryption scheme that supported the immediate attribute revocation was proposed.The scheme could achieve attribute-level user revocation and could effectively resist collusion attacks between the revoked users and the existing users.At the same time,this scheme outsourced complex decryption calculations to cloud service providers with powerful computing ability,which reduced the computational burden of the data user.The scheme was proved secure based on computational Diffie-Hellman assumption in the standard model.Finally,the functionality and efficiency of the proposed scheme were analyzed and verified.The experimental results show that the proposed scheme can safely implement attribute-level user revocation and has the ability to quickly decrypt,which greatly improves the system efficiency.